Is the time to task failure during severe-intensity exercise associated with muscle, blood, and respiratory changes? - Zagatto, Alessandro M. [UNESP]; de Poli, Rodrigo A B [UNESP]; Malta, Elvis S. [UNESP]; Fleitas-Paniagua, Pablo R.; Diefenthaeler, Fernando; Murias, Juan M.; Castro, Alex (American Physiological Society, 2025)
The study aimed to verify the physiological and metabolic parameters associated with the time to task failure (TTF) during cycling exercise performed within the severe-intensity domain. Forty-five healthy and physically active males participated in two independent experiments. In experiment 1, after a graded exercise test, participants underwent constant work rate (CWR) cycling efforts at 115% of peak power output to assess neuromuscular function (potentiated twitch) pre- and postexercise. Experiment 2 was similar to experiment 1, but with physiological (respiratory parameters, energetic pathway contribution) and metabolic parameters in the blood (gasometry and blood lactate responses) and vastus lateralis muscle tissue (target metabolomic analysis, glycogen content, muscle pH, and buffering capacity in vitro) measured instead of neuromuscular function. Experiment 1 evidenced a significant decrease in muscle force with instauration of peripheral fatigability indices and no change in central fatigue indices. Severe-intensity domain exercise in experiment 2 was accompanied by changes in physiological and metabolic parameters and in blood and muscle parameters. However, the TTF was associated with oxidative contribution (r = 0.811, P < 0.001), as well as anaerobic capacity (r = 0.554, P = 0.027), muscle buffering capacity (r = 0.792, P = 0.035), phosphagen energy contribution (r = 0.583, P = 0.017), and carnitine changes (r = 0.855, P = 0.016), but not correlated with electromyographic response, blood acid-base balance, and muscular glycogen content and pH. TTF during CWR exercise within the severe-intensity domain is likely explained by a combination of interacting mechanisms, with oxidative and phosphagen contributions, and muscle buffering capacity suggested as the main peripheral limiting factors to exercise within this exercise-intensity domain.NEW & NOTEWORTHY For the first time, a metabolomic analysis confirms that the cycling time to task failure (TTF) within the severe-intensity domain can be explained by muscle buffering capacity (62.2%), oxidative pathways contribution (65%), and muscle carnitine changes (71.9%), beyond some correlations with anaerobic capacity, tricarboxylic acid cycle intermediates, and phosphagen pathway contribution. The muscle glycogen content, muscle or blood pH, electromyography, and cardiorespiratory responses were not associated with TTF.
Keywords: cycling performance; metabolomic approach; muscle biopsy; task failure